Implementation of Gold Collateral Financing in Increasing Profitability at KSPPS BMT UGT Nusantara Pesanggaran Branch - Alfina, Risma Tahta; Zamroji, Yunus (UNIVERSITAS PAKUAN, 2024)
This research aims to determine the implementation of gold guarantee financing at the BMT-UGT Nusantara Pesanggaran branch in increasing profitability. Each sharia financial institution usually has varied marketing strategies to attract public interest. The strategy used by BMT-UGT Nusantara Pesanggaran Branch in developing gold collateral financing and to increase interest in the community is usually holding outreach. BMT-UGT Pesanggaran has prepared a financing product whose application is quite simple, so it is in great demand by the public. The contract used in this financing is rahn. This type of research uses descriptive qualitative research. The data source used in this research uses primary data obtained directly from research objects that have been determined to provide accurate information. The data collection techniques used in this research were interviews, observation and documentation. The conclusion obtained is that the implementation of gold guarantee financing at BMT-UGT Nusantara Pesanggaran Branch is quite easy and simple so that it is in great demand by the public.